INDIGENOUS INDIGENOUS PEOPLES AND THEIR LEGAL POSITION IN THE OMNIBUS LAW ON JOB CREATION: The Nature Of Indigenous Peoples - Muhammad Hatta Roma Tampubolon (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Indigenous peoples attach customary rights to themselves, namely rights owned by a legal alliance (such as Lipu, Boya, Ngata, Banua, etc.), where the citizens of the community (the legal alliance) has the right to control the land, the implementation of which is regulated by the head of the guild (the chief/village head concerned). Based on this right, the customary rights of indigenous peoples are basic rights inherent in the life of these people that are not a gift from the state. It is the same with the basic rights inherent in every human being, for example the right to life, which is not a gift of the state. Its legal position in the Job Creation Law which has the Character of omnibus law through juridical studies with a philosophical approach, conceptual approach, and a statutory approach. The right of indigenous peoples which is essentially the right to the value of justice and welfare value to the use of natural resources of indigenous peoples who not yet the maximum expected in the job creation law can provide justice and welfare for indigenous peoples over exploited customary territories. The logical consequence of the global trend and the strengthening of the ideology of neo-liberalism today is the emergence of a critique of the state welfare system that is seen as no longer appropriately applied as an approach in development of a country. The state welfare system is undergoing reformulation and adjustment in line with the demands of change, but it is very wrong to assume that the welfare of the state has met the end of its history. Therefore, the central government and local governments together with indigenous peoples to be able to open up and work hard to invite investors to invest in the regions and its territory, as the spirit of the job creation law, because the existence of investment strongly supports the running of the economy, but still pays attention to the rights of the MHA, namely: Rights on Land and Natural Resources (Customary Forests), The Right to Culture, The Right To Self-Determination, The Right To Free, Prior, Informed, Consend (FPIC).